Manejo das fraturas de côndilo mandibular - Pech, Grasielle de Lima (My University, 2019)
The treatment of mandibular condyle fractures has been controversial among oral and maxillofacial surgeons. This paper aims to review the current literature on the principles of treatment of condyle fractures, seeking to compare surgical and non-surgical treatment aiming at its advantages and disadvantages. A search was conducted in the PubMed and Scielo database, where 60 articles related to the treatment of mandibular condyle fractures were selected. From the selected articles, 27 articles were used that covered the principles of the treatment of these condylar fractures. The type of treatment of mandibular condyle fractures is directly related to the degree of aesthetic and functional impairment caused by the condylar fracture. Most surgeons are looking for the best treatment for these fractures, but it is known that we must take into account several factors for this decision. Both conservative treatment associated with maxillomandibular block and open reduction and internal fixation treatment have good aesthetic and functional results when well indicated. The degree of exaggerated dislocation, anatomical location, age of the patient and general health status are determining factors for choosing the ideal therapy. Therefore, it was noticed that both treatments have satisfactory results with no significant differences between them (sic).
O tratamento das fraturas de côndilo mandibular tem sido motivo de controvérsia entre os cirurgiões bucomaxilofaciais. O presente trabalho tem como objetivo revisar a literatura atual sobre os princípios de tratamento das fraturas de côndilo, buscando comparar o tratamento cirúrgico e não cirúrgico visando suas vantagens e desvantagens. Foi realizado uma pesquisa no banco de dados da PubMed e Scielo, onde foram selecionado 60 artigos relacionados ao tratamento das fraturas de côndilo mandibular. Dos artigos selecionados foram utilizados 27 artigos que abrangeram os princípios de tratamento dessas fraturas condilares. O tipo de tratamento das fraturas de côndilo mandibular está relacionado diretamente com o grau de comprometimento estético e funcional causado pela fratura do processo condilar. Grande parte dos cirurgiões buscam a melhor forma de tratamento para estas fraturas, mas sabe-se que devemos levar em consideração diversos fatores para essa decisão. Tanto o tratamento conservador associado ao bloqueio maxilomandibular quanto o tratamento por redução aberta e fixação interna possuem bons resultados estéticos e funcionais quando bem indicados. O grau de deslocamento exagerado, localização anatômica, idade do paciente e estado de saúde geral são fatores determinantes para a escolha da terapia ideal. Portanto, percebeu-se que ambos tratamentos possuem resultados satisfatórios não havendo diferenças significativas entre eles (sic).
Keywords: Odontologia; Condilo mandibular; Dentística operatória; Maxilares - Fraturas